Physicochemical behavior and supramolecular organization of polymers - Gargallo, Ligia (Springer, 2017)
As the title suggests, this monograph features the physicochemical behavior and supramolecular organization of polymers. The book consists of four chapters dealing with solution properties, viscoelastic behavior, physicochemical aspects at interfaces and supramolecular structures of polymeric systems. The classical treatment of the physicochemical behavior of polymers is presented in such a way that the book will meet the requirements of a beginner in the study of polymeric systems in solution and in some aspects of the solid state, as well as those of the experienced researcher in other types of materials. Physicochemical behavior and Supramolecular Organization of Polymers is ultimately, a contribution to the chemistry of materials; it is a powerful reference tool for students and scientists working both in polymer chemistry, polymer physics and materials science.